Lack of association between anatomical sites of scalp melanomas and brain metastases does not support direct vascular spread. Issue 4 (13th May 2022) - Li, Andrew T.; Miin Yip, Jia; Choksi, Harsham; London, Kevin; Potter, Alison J.; Lo, Serigne N.; Saw, Robyn P.M.; Shannon, Kerwin F.; Pires da Silva, Ines; Varey, Alexander H.R.; Menzies, Alexander M.; Long, Georgina V.; et al.
Abstract : Primary scalp melanomas are associated with a higher rate of brain metastasis than primary cutaneous melanomas occurring at other head and neck and body sites, but the reason is unclear. Spread to brain parenchyma via emissary veins draining from the scalp to dural sinuses has been suggested. We sought to examine the locations of metastases from primary scalp and nonscalp head and neck melanomas to determine whether there was anatomical evidence supporting direct venous spread to the brain. Data from patients who developed distant metastases from cutaneous head and neck melanomas (CHNMs) between 2000 and 2018 were analyzed. Anatomical sites of primary scalp melanomas and their respective intracranial metastases were compared. Times to first brain and nonbrain metastases were investigated for scalp and nonscalp primary CHNMs. Of 693 patients with CHNMs, 244 developed brain metastases: 109 (44.7%) had scalp primaries and 135 (55.3%) had nonscalp primaries. There was no significant association between anatomical sites of scalp primary melanomas and brain metastases (Cramer's V = 0.21; Chi-square P = 0.63). Compared with nonscalp CHNMs, scalp melanomas had no greater propensity for the brain as the first distant metastatic site ( P = 0.52) but had a shorter time to both brain metastasis (76.3 vs. 168.5 months; P < 0.001) and nonbrain metastasis (22.6 vs. 35.8 months; P < 0.001). No evidence was found to support a direct vascular pathway for metastatic spread of scalp melanomas to the brain. The increased incidence of brain metastases from scalp melanomas is probably driven by aggressive biological mechanisms.